The Development of the Principle of Litigation at Two Levels in the Saudi Judicial System - Alsubaie, Abdullah Eid (Journal of Economic, Administrative and Legal Sciences, 2022)
The study dealt with the issue of the development of the principle of two-levels litigation in the Saudi judicial system, and the research aimed to identify the nature of the principle of two-levels litigation and mention the importance of the principle of two-levels litigation, and a historical overview of it, and to point out some of the drawbacks to the principle of two- levels litigation. This principle through the stages of formation of the judicial system in the Kingdom of Saudi Arabia.The importance of the research was given that the importance of the principle of litigation on two levels lies in that it is a guarantee of access to the truth, and in order to achieve a judicial ruling expressing truth and justice with clarity and accuracy.The research followed descriptive, historical and analytical methods. Each in its appropriate location, according to the requirements of each requirement. And proceeded first of all to put forward the theoretical framework of the subject in general, to then address the descriptive presentation, and thus analyzed in order to conclude from then on the proposed results of the study.The research reached some results, the most important of which are: that the principle of a two- levels differentiation provides the opportunity for the litigants to raise the dispute again, which enhances confidence in the judicial system. The researcher also reached the importance of adopting this principle because it performs two important functions: the first is preventive, as it makes the judge slow down and wait and exert more care and effort Before it is issued, so that a judgment is not subject to criticism and response, and the second is remedial, where the errors of the court of first degree are corrected and corrected because the judges of the second court are more numerous and more experienced, that is, we avoid potential errors in the judiciary of courts of first degree.The research presented a number of recommendations, the most important of which are: Assigning researchers by research authorities to prepare research on the principle of litigation, and that the principle of litigation needs a jurisprudential adaptation from Sharia scholars, more accurate, and broader research, and highlighting the importance of the principle of litigation on two levels to the public as a guarantee for them, as well as the judiciary.
Keywords: the principle of litigation on two levels; courts of first degree; courts of second degree (appeal)